Pengaruh Fraksi Volume Serat Jerami Terhadap Kekuatan Material Komposit Aplikasi Kayu Lapis - Anggrek Oktaviameta; Kardiman Kardiman; Farradina Choria Suci (Politeknik Negeri Padang, 2021)
Polymer Matrix Composite (PMC) is a composite material that uses a polymer matrix most widely used in industry, transportation, and everyday life. Plywood is one of the current industrial needs that is growing rapidly and is becoming a leading export. However, besides that, the availability of raw materials is decreasing along with deforestation. Resulting in the need for alternative raw materials. Straw is one of the largest wastes that is not utilized optimally. It can be used as straw as a reinforcing material for environmentally friendly composite materials. Composite material was made using the hand lay up method, with straw fiber purchased with 4% NaOH treatment using Yukalac 157 BQTN-EX unsaturated polyester resin and MEPOXE A hardener. Then, tensile testing was carried out with volume fractions of straw fiber 5%, 10% 20% and 30 % This shows that the volume fraction of straw fiber affects the strength of the composite material. The tensile strength value of the straw fiber composite meets the minimum standard for tensile strength in plywood. Judging from the surface structure of the composite material, there are voids or air bubbles. However, the most visible in the sample with fractions of 10% and 20%. Further research needs to be done with other tests such as hit test, sandpaper test to meet the requirements for SNI standard plywood.